ความหลากหลายของพรรณพืชในพื้นที่ป่าปกปักมหาวิทยาลัยราชภัฏชัยภูมิ จังหวัดชัยภูมิ DIVERSITY OF PLANTS IN THE PROTECTION AREA OF CHAIYAPHUM RAJABHAT UNIVERSITY, CHAIYAPHUM PROVINCE - ณรัฐ จันทร์ศรี, สุรชัย; ชมภูพระ, ปารณีย์ (Srinakharinwirot University Journal of Sciences and Technology, 2021)
Plant diversity study was carried out in the protected area of Chaiyaphum Rajabhat University, Na-Fai Sub-District, Mueang District, Chaiyaphum Province, Thailand. The data were collected randomly from 32 sample plots (20x20 m2) during December 2016 to April 2017. The plants were listed by name with the analysis of diversity index and evenness. There were 85 species of plants in this area which included 57.65% of perennial plant, 12.94% of shrub, 18.82% of climber, 9.41% of herb and 1.18% of epiphytic plant. Seven species of perennial plants has the most relative frequency. However, only one species had been found for epiphytic plant. The area had an overall species diversity index of 3.48 which was at high level. The evenness was at 0.778 which was also quite high. The plant diversity index was 38.03 which indicated that 38 plant species have high survival rate from all 85 species in the study area.